Phenotypic effects of genetic variants associated with autism - Rolland, Thomas; Cliquet, Freddy; Anney, Richard J. L.; Moreau, Clara; Traut, Nicolas; Mathieu, Alexandre; Huguet, Guillaume; Duan, Jinjie; Warrier, Varun; Portalier, Swan; Dry, Louise; Leblond, Claire S.; et al. (Nature Medicine, 2023)
While over 100 genes have been associated with autism, little is known about the prevalence of variants affecting them in individuals without a diagnosis of autism. Nor do we fully appreciate the phenotypic diversity beyond the formal autism diagnosis. Based on data from more than 13,000 individuals with autism and 210,000 undiagnosed individuals, we estimated the odds ratios for autism associated to rare loss-of-function (LoF) variants in 185 genes associated with autism, alongside 2,492 genes displaying intolerance to LoF variants. In contrast to autism-centric approaches, we investigated the correlates of these variants in individuals without a diagnosis of autism. We show that these variants are associated with a small but significant decrease in fluid intelligence, qualification level and income and an increase in metrics related to material deprivation. These effects were larger for autism-associated genes than in other LoF-intolerant genes. Using brain imaging data from 21,040 individuals from the UK Biobank, we could not detect significant differences in the overall brain anatomy between LoF carriers and non-carriers. Our results highlight the importance of studying the effect of the genetic variants beyond categorical diagnosis and the need for more research to understand the association between these variants and sociodemographic factors, to best support individuals carrying these variants. Analyses of data from more than 200,000 individuals identify phenotypic features associated to carrying variants in autism-associated genes, in individuals with and without a diagnosis of autism.